2015
DOI: 10.1590/s1984-29612015023
|View full text |Cite
|
Sign up to set email alerts
|

Kudoa spp. (Myxozoa) infection in musculature of Plagioscion squamosissimus (Sciaenidae) in the Amazon region, Brazil

Abstract: Ninety specimens of Plagioscion squamosissimus captured using fishing tackle in the Outeiro district, state of Pará, were examined. Fish were placed in plastic bags containing water, under conditions of artificial aeration, and transported live to the Carlos Azevedo Research Laboratory (LPCA), in Belém, Pará. They were anesthetized, euthanized and necropsied; small fragments of the epaxial and hypaxial muscles were removed for examination of fresh histological sections by means of optical microscopy. In 100% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Cysts were diffusely distributed through the striated skeletal muscle fibers of 30% (12/40) of the specimens (Figure 1). Similar to that described by Eiras et al (2016) and Oliveira et al (2015), the parasites were located inside and between the muscle fibers. The spores were identified by light microscopies belonging to the genus Kudoa, based on characteristics including the quadrangular or pseudoquadrangular format, with the presence of four equal and pyriform polar capsules located side-by-side and the apex converging on the apical pole of spores, as described by Casal et al (2008) and Azevedo et al (2015) (Figure 2).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Cysts were diffusely distributed through the striated skeletal muscle fibers of 30% (12/40) of the specimens (Figure 1). Similar to that described by Eiras et al (2016) and Oliveira et al (2015), the parasites were located inside and between the muscle fibers. The spores were identified by light microscopies belonging to the genus Kudoa, based on characteristics including the quadrangular or pseudoquadrangular format, with the presence of four equal and pyriform polar capsules located side-by-side and the apex converging on the apical pole of spores, as described by Casal et al (2008) and Azevedo et al (2015) (Figure 2).…”
Section: Resultssupporting
confidence: 85%
“…Bunton and Poynton (1991) also observed a high prevalence (85%) of Kudoa spp. in Morone americana, Vaz (2000) reported prevalence of 84.7% in Trachurus trachurus and Oliveira et al (2015) reported prevalence of 100% by Kudoa sp in Plagioscion squamosissimus.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of the new species of parasite was 86%, a rate lower than those recorded in the silver croaker, Plagioscion squamosissimus, in which 100% of the specimens analysed by Oliveira et al (2015) were infected, or the spotted seatrout, Cynoscion nebulosus, in which 91% of the specimens examined by Dyková et al (2009) were infected with Kudoa inornata.…”
Section: Discussionmentioning
confidence: 62%
“…In the Amazon region, mixosporean of the genus Kudoa have been found infecting the muscle of Aequidens plagionatus (Casal et al 2008), Chaetobranchopsis orbicularis (Azevedo et al 2016, Sindeaux Neto et al 2017 and Plagioscion squamosissimus (Oliveira et al 2015), while in Hypophthalmus marginatus, Velasco et al (2015b) found this parasite in the muscle layer of the intestine. In the present study, we describe a new species, Kudoa viseuensis n.…”
Section: Introductionmentioning
confidence: 99%